SMOOTHNESS INDEX OF CENTRAL BLOOD PRESSURE AND PARAMETERS FOR VASCULAR STIFFNESS AFTER 20 WEEK TREATMENT WITH LOSARTAN PLUS AMLODIPINE VS. THIAZIDE RANDOMIZED TRIAL. (June 2018) - J.Shin,; Lee, H.Y.; Chung, W.J.; Youn, H.J.; Cho, E.J.; Sung, K.C.; Chae, S.C.; Yoo, B.S.; Park, C.G.; Hong, S.J.; Kim, Y.K.; Hong, T.J.; et al.
Abstract : Objective: With limitation of clinic and brachial BP, central BP and vascular parameters have known to be better to probe efficacy of antihypertensive drug. Because vascular parameters are measured at resting state, role of ambulatory central BP and vascular parameters to explain the difference in clinical efficacy between renin angiotensin system inhibitor in combination with amlodipine versus hydrochlorthiazide was uncertain. Design and method: As sub-study of multicenter randomized double blinded, losartan based therapy combined with amlodipine (LA) versus hydrochlorthiazide (LH), 143 patient (LH:73, LH:70) out of 220 patients with 80% or more valid readings in 24 hour ambulatory monitoring using Mobile-O-graph which provide ambulatory central BP and vascular stiffness data were analyzed. Smoothness index (SI) of SBP, central SBP(ACSBP), pulse pressure amplification(APPA), augmentation index(AAIx@75), and carotid femoral pulse wave velocity(AcfPWV). APPA was calculated by the ratio of SBP to ACSBP. Results: Age was 58.9 ± 12.3 years and female was 25.9%. Prevalence of drinking and current smoking were 51.5% and 21.7%, respectively. Diabetes mellitus was noted in 14.7%. Clinic BPs were 153.8 ± 10.2/92.4 ± 8.5 mmHg. Ambulatory 24 hour SBP and ACSBP were 136.5 ± 11.7 mmHg and 126.6 ± 11.0 mmHg. Changes in office BP was not different (LH:-15.2 ± 15.0/-7.8 ± 8.0 vs. LA:-14.9 ± 13.7/-9.2 ± 7.5 mmHg). Reductions of 24 hour SBP were greater in LA than LH (-10.3 ± 12.6 vs. -6.6 ± 10.2 mmHg, p = 0.0478). Only nocturnal ACSBP reduction was significant (LH:4.1 ± 12.2 vs. LA:9.4 ± 12.2, p = 0.01). And only nocturnal AcfPWV reduction was significant (LH:0.09 ± 0.41 vs LA: 0.26 ± 0.44 m/sec, p = 0.023). Intra-individual SIs for SBP and ACSBP were higher in LA than LH(SBP:-0.57 ± 0.78 vs. -0.39 ± 0.57, p = 0.0196; ACSBP:-0.57 ± 0.74 vs. -0.40 ± 0.57, p = 0.022). Intra-individual SI for AcfPWV were marginally significant (LH:0.31 ± 0.58 vs. LA:0.54 ± 0.77, p = 0.053). SIs for APPA and AAIx75 were not different. Intra-individual TP ratios were higher in LA than LH group but the differences are not significant for both SBP(0.30[95%CI, -0.07∼1.30] and ACSBP(0.24[95% CI, -0.51∼3.80]). Conclusions: LA combination seems to be superior to LH combination in reduction of ambulatory SBP. But for the reduction of ACSBP or AcfPWV was significant only in nighttime. Difference in intra-individual SI was significant both in SBP and ACSBP but not in AcfPWV. Further larger sample size studies are need